THE EFFECT OF SHIPPING FEE ON CUSTOMER RETENTION ON THE ONLINE SHOP IN MANADO - Walangarei, Christine (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
ABSTRACT Nowadays, online shops are becoming the most popular shopping style. In contrast with walk-in stores, online shops enthusiasts can shops throughout different cities and countries. With cheaper prices than walk-in stores, the online shop reach, the top of the world trade in a short time. Many buyers do not look at the price of the products but the shipping fees make them cancel to order. The reason is if the product is cheap then the shipping fee makes it expensive. Customers only buy once or twice then stop buying because the shipping fee makes them uncomfortable to buy from the online shop. The specific objective of this research is to examine the significant difference in customer retention between online shops with shipping fee and online shops without shipping fee. Theories supporting this research such as consumer motivation in shopping, customer retention, and shipping fee. The population of this research is shopper either shopping in-physical store or shopping in online store with sample as many as 100 respondents and sampling design is convenience sampling. Result and conclusion is there is a significant difference in customer retention between online shop without shipping fee and online shop with shipping fee. Keywords: customer retention, shipping fee